Learning Competencies among Students of Agriculture in Secondary Schools in Uasin-Gishu County, Kenya: A Value Chain Approach - Ouma, P.; Toromo, A.; Wanami, S.; Kabesa, S.; Mubichakani, J. (African Journal of Education,Science and Technology (AJEST), 2020)
Governments in Sub-Saharan Africa are undertaking education reforms to shift from knowledge-based learning to a curriculum that lays emphasis on technical and transferable skills. Despite the fact that over 90% of public secondary schools are taking agriculture in Kenya, food insecurity continues to be a major challenge raising the question of whether learners acquire the requisite competencies in agriculture. The aim of this research was to assess the learners’ skills and attitudes necessary to achieve the philosophy of teaching agriculture at the basic level of education in Uasin Gishu County. The specific objectives of this research were: to establish the instructional techniques used in teaching crop production practices and to determine the acquired learner competencies so as to prescribe possible ways of enhancing learner competencies in crop production for food security. A baseline study on the status of teaching and learning of crop production practices among schools in Uasin Gishu was conducted to establish the current status of teaching with a view to determine appropriate interventions that would be used by teachers of agriculture to respond to the needs of the Kenyan society. The study design was descriptive. Fourteen schools were purposively sampled to participate in the study. Questionnaires, interview schedule and observation checklists were used to collect data from the sampled respondents. Data was analyzed and presented using distribution tables and graphs. Findings showed that 46.2% of the teachers commonly used lecture method to teach general concepts in agriculture, 30.8% use student activity while 15.4% use demonstration method. Specifically, demonstration was used by 76.9% of the teachers to teach only planting while 56.3 % of students indicated that teachers explained most practical activities theoretically. In terms of enthusiasm, it was noted that 35.7% of the students’ leadership skills were below expectation. There was no significant relationship between the teaching method and the competencies manifested by learners (P (χ2=2.266, df 8) =0.972 at α 0.05). Based on the current teaching approaches, the learners of agriculture did not seem to acquire any competencies that they would transfer in agricultural production in the society. Recommended interventions should include experiential learning targeting high value crops and post-harvest handling.